Interleukin-7 receptor Thr244Ile gene polymorphism and the risk of systemic lupus erythematosus - Jagodzinski, Pawel Piotr; Piotrowski, Piotr; Olesińska, Marzena (Journal of Medical Science, 2016)
Aim. Recently, the IL-7 receptor (IL-7R) C>T (rs6897932) single nucleotide polymorphism (SNP), which causes a Thr244Ile substitution in the IL-7R ?-chain, has been suggested as a risk factor for SLE.Material and Methods. Using high-resolution melting curve analysis we studied the distribution of the IL-7R C>T polymorphism in SLE patients (n = 281) and control subjects (n = 541) in the Polish population.Results. We did not find significant differences in the distribution of the IL-7R C>T genotype and alleles between SLE patients and controls. However, in the dominant model (T/T and C/T vs C/C genotypes), we observed a protective effect of the IL-7R C>T polymorphism against the presence of neurological manifestations of SLE [OR = 0.3631 (95% CI = 0.1895–0.6954), p = 0.0017, pcorr = 0.0323] and the presence of anti-Scl-70 antibodies (Ab) [OR = 0.3141 (95% CI = 0.1503–0.6561), p = 0.0014, pcorr = 0.0266].Conclusion. Our studies suggest that the IL-7R C>T (rs6897932) polymorphism might be involved in the neurological manifestations and the presence of anti-Scl-70 Abs in patients with SLE.
Keywords: Interleukin-7 receptor; SNP; SLE